DETERMINANTS OF FDI INFLOWS IN SIX ASEAN COUNTRIES IN 1998-2016 - Iqbal Firdaus; Sri Mulatsih; Iskandar Ahmaddien (Universitas Pasundan, 2019)
Investment is an important element of the growth and the development of economic. Foreign DirectInvestment (FDI) is one of the investment sources as an alternative to the Domestic Investment thatmight be difficult to be fulfilled by a country itself. The increased numbers of FDI inflows toASEAN countries turns out were not evenly distributed to each country. This research is importantto determine the development and determinants of FDI inflows in six ASEAN countries in the periodof 1998-2016. From the panel data regression analysis, it can be concluded that the variable levelsof corruption negatively affect the FDI inflows, while the level of economic freedom and incomeper capita has a positive effect on FDI inflows in six ASEAN countries in 1998-2016.